Differential immunostaining of various types of breast carcinomas for growth hormone‐releasing hormone receptor – Apocrine epithelium and carcinomas emerging as uniformly positive. Issue 9 (31st January 2014) - Kővári, Bence; Rusz, Orsolya; Schally, Andrew V.; Kahán, Zsuzsanna; Cserni, Gábor
<x xml:space="preserve">Abstract</x> Different classes of breast cancers were explored for their positivity for growth hormone‐releasing hormone receptors (GHRH‐R) in this pilot study, as no systematic evaluation of such tumors has been performed to date. Seventy‐two small primary breast carcinomas were evaluated for GHRH‐R expression by immunohistochemistry using a polyclonal antibody and a cutoff value of 10% staining. GHRH‐R positivity was detected in 58% of all cases, 20/23 (87%) of invasive lobular carcinomas (ILC) and 22/46 (48%) of invasive ductal carcinomas (IDC). GHRH‐R positivity was more frequent in grade 2 tumors (86%), as compared to grade 1 (18%) or grade 3 (47%) cancers. GHRH‐R expression was not associated with mitotic scores, the Ki‐67 labeling indices or nodal status. IDCs with casting‐type calcifications on the mammogram showed positivity for GHRH‐R in 9/12 (75%) cases. Most importantly, apocrine epithelium, and all 10 apocrine carcinomas added later to the study were GHRH‐R‐positive. These preliminary results suggest a greater than average GHRH‐R expression in ILCs and IDCs associated with casting‐type calcifications on the mammogram. Apocrine carcinomas seem uniformly positive for GHRH‐R. Whether these findings could indicate a potential role of GHRH‐antagonists in targeted treatment of these types of breast cancer requires further studies.